Morphology of glandular stomach (Ventriculus glandularis) and muscular stomach (Ventriculus muscularis) of the partrigde Rhynchotus rufescens - Juliana Regina Rossi (Ciência Rural, 2005)
Twenty adult partridges Rhynchotus rufescenswere used for morphologic and histological study. Thematerials destined to the morphologic study were collectedand the lengths of the glandular stomach and of the muscularstomach were measured. For the histological study, fragmentsof the glandular stomach (gastric proventriculus, ventriculusglandularis) and of the muscular stomach (gastric ventriculus,ventriculus muscularis) were stained routinely with periodicacid-Schiff (PAS) and Massons trichrome stain. Glandularstomach is prolonged, with a fusiform format towardcraniocaudalis and for the left. It presents a mean length of3.20cm in the females and 3.65cm in the males. Gastricproventriculus is composed by several lobes and glands. Themucosa is formed by a simple cubic epithelium, which ismuch folded. Muscular stomach has the format of a biconvexlens, with 4.30cm and 4.35cm of mean length for the femalesand male, respectively. The mucosa is formed by folds linedby columnar cells and the mucus that forms the cuticula.There are crypts in the base of the folds. Closely, there is alamina propria and a thick smooth muscle layer, which isplaced according to the format of the organ. A dense portionof connective tissue constitutes the serosa, mixed by somesmooth muscle cells.